Intravesical injection of peripheral blood mononuclear cell for the treatment of interstitial cystitis: A preliminary report - Ching-Pei Tsai; Kai-Lun Cheng; Evelyn Yang; Lung-Yung Huang; Fu-Hui Wang; Man-Jung Hung; Hong-Lin Su (PLoS ONE, 2025)
Interstitial cystitis (IC) is a complex syndrome characterized by symptoms such as bladder pain, urgency, frequency, and nocturia, without the presence of urinary tract infection or any other identifiable pathology. Traditional treatments, including medication and bladder instillation, are often ineffective in about 30% of patients. Currently, efforts are focused on developing therapies based on the possible pathogenesis of IC. This study is a phase one clinical trial which aimed to investigate the safety and efficacy of autologous peripheral blood mononuclear cell (PBMC) intravesical injections, which have the potential to promote tissue regeneration, as a novel treatment for IC. The study involved isolating PBMCs using the Sepax Cell Separation System and injecting these cells beneath the bladder mucosa layer of patients with IC. Clinical efficacy was evaluated using voiding diaries, questionnaires, and cystoscopic examinations before and 3 months after treatment. Twelve patients with refractory IC participated in this study. Observed side effects, such as pain or urinary tract infection, were mild and transient which demonstrated the safety of this treatment modality. Although the treatment response varied among patients, a third of the patients experienced moderate to significant progress according to the GRA score. Four patients exhibited improvement in bladder glomerulations during postoperative follow-up cystoscopy. In conclusion, the overall safety profile of PBMCs injections appears to be favorable. Further research is needed to optimize treatment protocols and understand the factors influencing individual responses to this therapy.